Pengaruh Program Mamah & Aa Beraksi di Indosiar terhadap Meningkatnya Pengetahuan Agama (Survey kepada Masyarakat Rw.010 Sunter Agung) - Hesty Dwi Cahyani; Salman (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Religious programs at Indosiar are very diverse in providing knowledge about religion, one of them is a religious talk show program that is Mamah & AA Beraksi. This study aims to determine whether there is an influence of the Mamah & AA Beraksi Program In Indosiar Towards Increasing Religious Knowledge and how strong the influence of the Mamah & AA Beraksi Program In Indosiar. This research uses cultivation theory, this research uses positivistic paradigms and quantitative approaches and types of explanative research. With data collection techniques such as questionnaires and analyze data using Pearson Correlation, Simple Linear Regression Test and Hypothesis Test. Based on the results obtained from the analysis of the correlation results of 0.665 which means brings a strong relationship on both variables and hypothesis testing of 8.504 results obtained from the 93 respondents research, after that the value of t table 1.986 with df = 93 - 2 = 91. Then it can be concluded that Ho is rejected and Ha is accepted in other words there is the Effect of Mamah Program & AA Beraksi In Indosiar Towards Increasing Religious Knowledge.